The Use of Powtoon in Teaching Reading Recount Text - Fitri, Rika Al (English Language Education, Universitas Internasional Batam, 2022)
This research is motivated by the development of Powtoon-based learning media. Powtoon media is a web-based application provided for users to create animated presentations using images, provide music. The advantage possessed by powtoon media is that it is able to provide various animated cartoon displays that can attract students' attention to pay attention to the lessons delivered by the teacher. Lessons for the 2021/2022 academic year. This classroom research was carried out in three meetings. The author used one group pre-test and post-test design. Respondents in this study were 4 students of class X IPS-1. The results of this study. Based on the research that has been done, it can be proven by using the results of the pre-test score obtained that has a score of 50,75 and the post-test score has 75,25. The test score has increased with an increase in value of 24,05. Based on this research, it is proven that learning by using video powtoon will have an effect on increasing learning outcomes. Therefore, the powtoon learning media is proven to be able to improve learning outcomes, especially for class X students on recount text.